Fate of Parasites and Viruses in Calcium Hydroxide-Treated Urine in Relation to Temperature and Moisture Content - Senecal, Jenna; Nordin, Annika Christina; Decrey, Loïc; Kohn, Tamar; Vinnerås, Björn (Frontiers in Environmental Science, 2022)
Human urine can be used as fertilizer and technologies, such as alkaline-urine treatment, are being developed to enable easier re-use. There is, however, a risk of pathogens being present in the urine. This hygiene assessment examined inactivation of three model organisms, one parasite (Ascaris suum) and two viruses (coliphages MS2 and ΦX174), during (1) alkaline-urine treatment and (2) drying of the alkalized-urine (A. suum only). Fresh human urine was mixed with calcium hydroxide (10 g Ca(OH)2 L-1 urine) and divided into three fractions (Mixed liquor, Supernate, Precipitates). The factions were inoculated with the model organisms and then subjected to three treatments (Drying-storage, Stored and Thermal treatment) at temperatures between 20 and 50 °C. For Ascaris, drying (moisture content (MC) 13-33%) the alkaline-urine proved effective in shortening the time required for a 3 log10 reduction in viable eggs at 20 °C, but only Partially drying (MC 73-82%) the urine led to longer inactivation times compared with Wet (MC >90%) or Dry conditions. While virus inactivation took place during the initial addition of Ca(OH)2, the viruses that were embedded in feces survived longer compared to the free viruses. At pH 11.5, contact times of 1.5 and 90.7 min were required to achieve a 4 log10 decay of phages in solution and phages embedded in feces respectively. In areas prone to parasites, Thermal treatment (≥42 °C) and/or Storage (111 days at 20 °C or 79 days at 35 °C) is recommended in order to meet the WHO and USEPA guidelines for unrestricted fertilizer use. Drying (MC 73-82%) can also be used in combination with thermal treatment and/or storage, to accelerate the process.